Exploring farmers’ ecological knowledge and agro-chemical practices for sustainable food security and health in Ghana: a narrative review - John Bosco Baguri Sumani; Justice Aduko; Suleman Mula (Discover Agriculture)
Abstract Agriculture in Ghana is at a crossroads, with farmers’ ecological knowledge—a reservoir of traditional wisdom—being increasingly overshadowed by the widespread adoption of agro-chemicals. This narrative review examines the intricate yet complex relationship between farmers’ ecological knowledge and agro-chemical practices, focusing on their impact on food security, health outcomes, and environmental sustainability. This study highlights the dual roles of agro-chemicals in boosting agricultural productivity and worsening long-term environmental and health risks. The review identifies critical gaps in farmer education, regulatory enforcement, and the integration of indigenous knowledge with scientific advancements. The study’s novelty lies in its holistic approach to bridging traditional ecological knowledge with modern agricultural technologies, offering a unique framework for sustainable farming systems in Ghana. Unlike prior studies that narrowly examined either agro-chemical impacts or traditional practices separately, this research integrates both perspectives, addressing policy and practice gaps to promote a resilient agricultural system. The study also acknowledges its limitations, including reliance on secondary data and the lack of region-specific empirical case studies, which present opportunities for future research. This work makes a significant contribution to achieving the United Nations Sustainable Development Goals, particularly SDG 2 (Zero Hunger), SDG 3 (Good Health and Well-being), and SDGs 13 and 15 (Climate Action and Life on Land). It provides actionable insights for policymakers, researchers, and stakeholders, thereby advocating a paradigm shift toward sustainable agriculture that harmonizes tradition with modern scientific innovation.